Investigation of numeracy proficiency levels among elementary students through the PEMANTIK assessment tool - Soesanto, Robert Harry; Dirgantoro, Kurnia Putri Sepdikasari (Universitas Papua, 2024)
Mathematics education is critical in nurturing a wide range of cognitive abilities, particularly numeracy skills, which are essential for students’ everyday lives. This study aimed to systematically evaluate the numeracy levels of elementary students at Lentera Harapan School (LHS) in Indonesia using the PEMANTIK assessment tool. A cross-sectional design with a phenomenological approach was applied, encompassing 4,279 students from Grades 1 to 6. The assessment tool comprised a numeracy test accessed through PEMANTIK, and the resulting data were analyzed using descriptive statistical techniques to map numeracy levels across different grades. Findings revealed that students in Grade 3 and above faced significant challenges in developing numeracy skills. The study also highlighted LHS's commitment to implementing evidence-based practices and pedagogical strategies to help teachers support students' numeracy skill development.